2020
DOI: 10.1371/journal.pone.0239582
|View full text |Cite
|
Sign up to set email alerts
|

The role of duration and frequency of occurrence in perceived pitch structure

Abstract: Introduction To survive, organisms need to organize perceptual input into coherent, usable structures. Research has illuminated the potential role of frequency of occurrence and duration as cues to extract statistical regularities from our environment. Musical stimuli provide a unique opportunity to study how these cues are used to organize auditory input into higher level perceptual entities, i.e., pitch structure, and to assess the influence of cognitive schema. Methods To examine the relative importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 111 publications
1
5
0
Order By: Relevance
“…Perceptual experiments generally support the suggestion that probe-tone ratings reflect types of musical emphasis other than frequency of occurrence, such as closure (Aarden, 2003), metric stress (Prince, Thompson, & Schmuckler, 2009;Rosenthal & Hannon, 2016), and duration (Lantz & Cuddy, 1998;Lantz & Cuddy, 2006). The current study joins previous work (Aarden, 2003;Prince & Schmuckler, 2014) in providing corpus evidence that converges on a similar conclusion.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Perceptual experiments generally support the suggestion that probe-tone ratings reflect types of musical emphasis other than frequency of occurrence, such as closure (Aarden, 2003), metric stress (Prince, Thompson, & Schmuckler, 2009;Rosenthal & Hannon, 2016), and duration (Lantz & Cuddy, 1998;Lantz & Cuddy, 2006). The current study joins previous work (Aarden, 2003;Prince & Schmuckler, 2014) in providing corpus evidence that converges on a similar conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…The possibility that rhythmic duration and raw frequency counts make independent contributions to tonal hierarchy judgments is implicitly acknowledged in the decision to use total chromatic scale degree duration as the basis for the Krumhansl-Schmuckler key finding algorithm (Krumhansl, 1990; Krumhansl & Schmuckler, 1986). Subsequent analysis has found that durational weighting does seem to improve Krumhansl-Schmuckler and derivative key finding algorithms (Madsen & Widmer, 2007) while perceptual experiments have suggested that duration can be a more salient cue of tonal hierarchy than frequency in both novel (Lantz & Cuddy, 1998; Lantz & Cuddy, 2006) and familiar (Smith & Schmuckler, 2004) tonal contexts. Drawing on Aarden’s (2003) finding that probe-tone profiles correspond to scale degree frequencies in phrase-final positions, the use of percentage of scale degree occurrences in phrase-final positions opts for a related measure that, unlike frequency of scale degree occurrences in phrase-final positions, is not necessarily related to global frequency counts.…”
mentioning
confidence: 99%
“…Developmental 8 , 9 , cross-cultural 10 , 11 , and laboratory data 12 , 13 show that musical knowledge is gained about the music in one’s environment. Other studies have extended this research by showing that this knowledge exerts influence on the perception of incoming tone sequences 14 , 15 . For example, when presented with intervals of two notes in the context of diatonic tone sequences, listeners’ perception of the distance between the two notes is influenced by the structural relationship between the two notes in diatonic music 16 .…”
Section: Introductionmentioning
confidence: 63%
“…The frequency of safety training offers organizational management assistance in structural and cost-effective training management, as well as legal compliance. The frequency of safety training is periodic and continuous, and also requires a specific schedule and time interval [82,83]. Regular safety training should be provided to ensure that knowledge and skills are kept up to speed with the newest technology and current advancements.…”
Section: Discussionmentioning
confidence: 99%